Immunotherapeutic Effect of Rasayanas in Cancer: A Conceptual Study - Dhatri Datta; Jayanthi. C; Santhosh Patil (International Journal of Ayurveda and Pharma Research, 2022)
The natural repertory of the normal human immune system’s NK and T cells, as well as pharmacological elaborations, includes killing tumour cells. Aggressive human malignancies, on the other hand, are selected by the host immune system’s death of sensitive tumour cells and the survival of immune-resistant cancer cells. The capacity of these cells to evade “normal” immune killing actions could be a primary cause of malignancy progression, resulting in clonal growth, metastases, and patient death. The Ayurvedic idea of Vyadhikshamatwa, (Immunity) which re-engages the immune system to stage a counter-revolution, lays the path for a considerable clinical improvement in overall survival of patients with enhanced quality of life. Strategies like Rasayana Chikitsa can help to boost attempts to remove immune suppression in tumours by rousing dormant T-cell activity and restoring immune surveillance, especially when combined with chemotherapy and radiotherapy. The study uncovers aspects of cancer, immunotherapy, Ayurvedic aspects of Immunity and evidence of Immunotherapeutic properties of Rasayanas. Immunostimulatory immunotherapy, such as Rasayana Chikitsa, is the focus of this work which could show to be highly effective by restoring the patient’s inherent immune powers, opening up a new therapeutic front in the clinical arena of Cancer. Although the clinical studies are limited, the present study hope towards more approvals and wider usage of Rasayana Chikitsa in Cancer.